The Oxford Handbook of Mood Disorders 2016
DOI: 10.1093/oxfordhb/9780199973965.013.30
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Syndromes and Medical Comorbidities

Abstract: The prevalence of depression is substantial among individuals with medical conditions and is associated with poorer treatment outcome for both the mood disorder and medical condition. This chapter examines the prevalence, risk factors, causal associations, and treatment for depression in four medical conditions: cancer, cardiovascular disease, multiple sclerosis, and HIV/AIDS. Several conclusions are evident: First, depression is unrecognized in about 30% of medical patients, and twice as many medical patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This study showed that participants with skin disorders along with comorbid medical conditions were more likely to have depressive symptoms. This is in agreement with the psychosomatic view that physical illnesses tend to impact mental disorders and, conversely, that mental disorders impact physical illnesses . This observation could be explained by the psychological and neurobiological impact of these chronic medical conditions that may lead to the development of depression .…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that participants with skin disorders along with comorbid medical conditions were more likely to have depressive symptoms. This is in agreement with the psychosomatic view that physical illnesses tend to impact mental disorders and, conversely, that mental disorders impact physical illnesses . This observation could be explained by the psychological and neurobiological impact of these chronic medical conditions that may lead to the development of depression .…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the psychosomatic view that physical illnesses tend to impact mental disorders and, conversely, that mental disorders impact physical illnesses. 6,56,57 This observation could be explained by the psychological and neurobiological impact of these chronic medical conditions that may lead to the development of depression. 58 Furthermore, medications used to treat these disorders may affect the patients' neurochemical balance, which in turn can precipitate depressive illness.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, health adherence, health behaviors, machine learning COVID-19 ADHERENCE | bs_bs_banner health behaviors has shown that mental health challenges such as anxiety and depression interfere with efforts to engage and persist with health behaviors (Hopko et al, 2017;Katon & Ciechanowski, 2002). On the other hand, those with greater health anxiety or worry might be expected to engage in health behaviors more fully.…”
Section: Introductionmentioning
confidence: 99%